Effect of biotic, abiotic and botanical inducers on crop growth and severity of brown spot in rice - S.K. BISWAS, CHINMAY BISWAS*, S.S.L. SRIVASTAVA, (Indian Phytopathology, 2010)
The pre-treatment with Trichoderma viride, T. hazianum, hydrogen peroxide, calcium chloride, K2HPO4 and leaf extracts of neem and datura reduced the number of brown spot lesions per leaf as well the per cent disease index. The reduction of disease severity was highest by T. harzianum (70.8%) followed by T. viride (68.8%), calcium chloride (67.1%), K2HPO4 (64.5%), datura (61.7%), hydrogen peroxide (53.5%) and neem (41.2%). With reduction of disease severity the inducer treatments also promoted the crop growth. In 30 days old rice plants, the shoot length was increased by 31.5-75.7% and the root length by 33.2-72% over the diseased check by different inducer treatments.